Analisis Opsen Pajak Kendaraan Bermotor di Kota Kupang Berdasarkan Undang – Undang Nomor 1 Tahun 2022: Studi Kasus pada Samsat Kota Kota Kupang - Gresia Irene Yomar Lakabela; Markus A.K.B. Hallan; Siprianus G. Tefa (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The purpose of this study is to analyze the implementation of the motor vehicle tax option in Kupang City based on Law No. 1 of 2022, examine its impact, and assess the effectiveness of the tax option policy. The study used a qualitative method with data collection techniques through library and field studies. Data analysis used the NVivo application. The results of the study stated that the implementation of the PKB option policy in Kupang City was in accordance with the provisions of the law and strengthened by Regional Regulation No. 1 of 2024. This policy provides fiscal authority for the Kupang City government in direct receipt of the motor vehicle tax option (PKB). The impact of the motor vehicle tax option policy can be seen from the increase in taxpayer compliance as indicated by the increasing number of motor vehicles from year to year. In addition, the option is also effective in increasing Regional Original Income (PAD) in Kupang City, especially in financing infrastructure and public services. The results of this study confirm that the motor vehicle tax option policy is a strategic instrument in strengthening regional fiscal independence, although it requires socialization, transparency, and quality of public services.